The Comparative Study of Shrimp Drying Process with Low Humidity Air and Hot Air Drying: - - วิสัยพรม ณัฏฐวัฒน์; กาศยปนันทน์ ณัฏฐ์; พลาศัย วสันต์ (Princess of Naradhiwas University Journal, 2019)
The objectives of this research were to investigate the factors that affect the drying process of shrimp by using Relative Humidity Air Drying method compared with Hot Air Drying. Resilience, water activity, and other variables, were controlled by temperature and relative humidity control in a low humidity drying room at 30 oC and 35 - 55% Rh, respectively, while the hot air drying process was carried out at 40, 50 and 60 oC. The physical properties of the shrimp such as color, hardness, texture, temperature, and moisture content, were determined. Drying with hot air using a drying temperature of 60 oC took a minimum of 150 minutes to dry. The final moisture content of the shrimp was 13.51 (% d.b). The brightness was 49.52 ± 2.01, compared to other drying methods, for which values were not significantly different (p <0.05). It was found that hot air drying had the highest hardness value (154.33 N), along with a low relative humidity of 118 N for water activity, in the range of 0.5-0.6, which was not higher than the standard for product (136/2558) set by Thai Industrial Standards Institute.